2003
DOI: 10.1042/bj20021401
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of Bacillus thuringiensis Cry proteins on mammalian cells transfected with cadherin-like Cry receptor gene of Bombyx mori (silkworm)

Abstract: Cry1Aa, an insecticidal protein produced by Bacillus thuringiensis, has been shown to bind to cadherin-like protein, BtR175, in Bombyx mori (silkworm) midgut. We previously reported three variant alleles of BtR175 (BtR175a, b and c). When transiently expressed in COS7 cells, all the three BtR175 variants bound to Cry1Aa. We stably expressed BtR175b in HEK293 cells. These BtR175b-expressing cells swelled and died in the presence of activated Cry1Aa in a dose- and time-dependent manner, showing that BtR175b itse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 26 publications
4
35
0
Order By: Relevance
“…1B and Movie 1). Cell swelling and lysis occurred within a short time frame (30-40 min after toxin exposure), a phenomenon also observed in other insect cells (9,40) as well as in mammalian cells transfected with the cDNA of BT-R receptors (11). The morphological changes observed in Cry1Ab toxin-treated cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…1B and Movie 1). Cell swelling and lysis occurred within a short time frame (30-40 min after toxin exposure), a phenomenon also observed in other insect cells (9,40) as well as in mammalian cells transfected with the cDNA of BT-R receptors (11). The morphological changes observed in Cry1Ab toxin-treated cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…The specificity of Cry toxins depends on individual cell surface receptors, which represent a family of cadherins expressed in the midgut epithelium of various insects (9)(10)(11)(12)(13). Cytotoxicity and cell death are the direct result of univalent binding of a Cry toxin monomer to its respective cadherin receptor (14).…”
mentioning
confidence: 99%
“…In another study, Cry1Aa caused cell swelling and cytotoxicity in mammalian cells expressing BtR175b (an allelic variant of BtR175) (171). Cry1Ab and Cry1Ac had similar albeit weaker effects, in correlation with their lower binding affinities for BtR175 (80,171). This work demonstrated that BtR175 could confer Cry1A susceptibility outside of an insect system and made it possible to rule out the requirement for other insect specific factors in cytotoxicity.…”
Section: Btr175 (Bombyx Mori)mentioning
confidence: 85%
“…The cadherin-like protein BtR175 from Bombyx mori serves as a Cry1Aa receptor (12), and when expressed in Sf9 cells it promotes swelling after exposure to Cry1Aa toxin because of formation of ion channels in cell membranes (13). When expressed in mammalian COS-7 cells, BtR175 induced susceptibility to Cry1Aa (14). Elimination or alteration of cadherin-like proteins from the midgut correlates with insect resistance to B. thuringiensis Cry proteins in Heliothis virescens (15) and Pectinophora gossypiella (16).…”
mentioning
confidence: 99%